1995
DOI: 10.1038/jcbfm.1995.93
|View full text |Cite
|
Sign up to set email alerts
|

Differences in DNA Fragmentation following Transient Cerebral or Decapitation Ischemia in Rats

Abstract: Summary:The time course of appearance of cells with DNA damage was studied in rats following transient se vere forebrain ischemia. This DNA damage could be de tected by in situ end-labeling on brain sections. The breaks in DNA appeared selectively by day I in the stri atum and later in the CAl region of the hippocampus. It was possible by double labeling to show that there was no DNA damage in astrocytes. The DNA breaks consisted of laddered DNA fragments indicative of an ordered ap optotic type of internucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
50
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(52 citation statements)
references
References 50 publications
2
50
0
Order By: Relevance
“…These have been in both global (Fer rer et al, 1994;Heron et al, 1993;Iwai et al, 1995;Nitatori et al, 1995;Okamoto et al, 1993;Tortosa et al, 1994) and focal (Li et al, 1995a-c; Linnik et al, 1993 andTominaga et al, 1993;Sei et al, 1994) models of transient brain hemostasis. Some of this evidence came from this laboratory, where we concluded that a component of the apoptotic degra dative machinery is at work in the ischemic neurons (Hill et al, 1995;MacManus 1993MacManus , 1994MacManus , 1995a. In general, an absence of the morphological hallmark in ischemic brain has precluded wide acceptance of an apoptotic mode of cell death being operative fol lowing ischemia (Deshpande et al, 1992).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These have been in both global (Fer rer et al, 1994;Heron et al, 1993;Iwai et al, 1995;Nitatori et al, 1995;Okamoto et al, 1993;Tortosa et al, 1994) and focal (Li et al, 1995a-c; Linnik et al, 1993 andTominaga et al, 1993;Sei et al, 1994) models of transient brain hemostasis. Some of this evidence came from this laboratory, where we concluded that a component of the apoptotic degra dative machinery is at work in the ischemic neurons (Hill et al, 1995;MacManus 1993MacManus , 1994MacManus , 1995a. In general, an absence of the morphological hallmark in ischemic brain has precluded wide acceptance of an apoptotic mode of cell death being operative fol lowing ischemia (Deshpande et al, 1992).…”
mentioning
confidence: 99%
“…Since our own studies showed that apoptotic laddered DNA appeared in brain following transient ischemia (Hill et al, 1995;MacManus et al, 1993MacManus et al, , 1994MacManus et al, , 1995a, we undertook to detect higher-order chromatin fragments. While these studies were in progress [described in abstract form in MacManus et al (1995b)], a report appeared describing the appearance of 300-kbp fragments of DNA following ischemia produced by middle cerebral artery occlu sion, with evidence of subsequent breakdown to smaller pieces (Charriaut-Marlangue et al, 1995).…”
mentioning
confidence: 99%
“…T he mechanism by which stroke-induced neuronal death occurs is complex and is likely dependent upon the severity and duration of ischemic insult and an elaborate interplay between ischemic death initiators such as excitotoxicity, oxidative stress, DNA damage, and inflammatory responses (1)(2)(3). Neurons that survive the acute ischemic injury undergo a delayed cell death that exhibits some characteristics of apoptosis (1)(2)(3).…”
mentioning
confidence: 99%
“…Neurons that survive the acute ischemic injury undergo a delayed cell death that exhibits some characteristics of apoptosis (1)(2)(3). This delayed cell death is dependent upon selected death-signaling elements such as caspases, poly(ADP-ribose) polymerase, and p53 (4).…”
mentioning
confidence: 99%
“…Apoptosis has been detected in the brains of several mammalian species, including human infants, after HI (Linnik et al, 1993;MacManus et al, 1993MacManus et al, , 1995Mehmet et al, 1994;Li et al, 1995;Beilharz et al, 1995;ChariautMarlangue et al, 1995;Edwards et al, 1997;Yue et al, 1996). Recent in vitro data have stressed the role of energy metabolism and the mitochondria in controlling apoptosis (Liu et al, 1996;Yang et al, 1997), but suggested that apoptosis results from a mild cellular insult, while severe stress induces necrosis .…”
Section: Introductionmentioning
confidence: 99%